PEMBENTUKAN KARAKTER DISIPLIN SISWA MELALUI PENERAPAN TATA TERTIB SEKOLAH DI SEKOLAH MENENGAH PERTAMA BUDI MULIA PAKISAJI MALANG - Khoiroh, Nikmatul (JIPI (Jurnal Ilmiah Pendidikan Islam), 2022)
This study aims to determine how the formation of student discipline character through school rules at SMP Budi Mulia Pakisaji Malang and what are the supporting and inhibiting factors. This research uses qualitative research with case study method. The data collection technique is by observation, interview and documentation. The results of this study indicate that the application of the student discipline character at SMP Budi Mulia has been running well and maximally with te support of all school, resulting in students who have a discipline character. The implementation carried out by the school in the application of school rules to shape the character of student discipline is to carry out, habituation, socialization, example, sanctions (punishment), supervision, and evaluation. These various strategies produced good result, namely student discipline which was increasing from the previous time. Keywords : Character, Discipline, Order